Perancangan Enterprise Architecture Pendaftaran Uji Kir Menggunakan FEAF di DISHUB Kab.Sukabumi - Asep Sutiawan; Risa Sri Marlianti; Salsa Tini Kareksi; Sudin Saepudin (Seminar Nasional Informatika (SEMNASIF), 2020)
AbstractThe kir test is a vehicle test that is carried out on vehicles with rental transportation status. This test is a technical requirement and a manifestation of security, safety, order and smoothness of traffic and is recorded in articles 48 - 55 of Law no. 22/2009. The registration process that runs at the Sukabumi Regency Transportation Service is still fairly manual and has not been facilitated by the system so that the services provided are still not optimal, with an average registration number of 90-100 registrants per day that can even exceed the quota provided, the Sukabumi Regency Transportation Service providing registration time starting from 08.30 am to 12.00 noon, but the number of registrants and registration time is not appropriate, causing registration counter officers to be overwhelmed in managing the queue and often causing long queues, it is not uncommon for registrants who do not get the Test schedule due to the schedule which was full that day, so it must come again the next day. Due to these various problems, an enterprise architecture design for registration test will be made using the Federal Enterprise Architecture Framework (FEAF) at the Sukabumi District Transportation Office.The result of this research is to make a system design for registration test, in the form of semantic models, activity diagrams, use case diagrams, network architecture designs, and database designs required for system development, as well as prototype of the registration test registration system.Keywords: Enterprise Architecture Design, Kir Test, FEAF (Federal Enterprise Architecture Framework).AbstrakUji kir merupakan pengujian kendaraan yang dilakukan terhadap kendaraan dengan status angkutan sewa. Pengujian ini merupakan persyaratan teknis dan perwujudan keamanan, keselamatan, ketertiban, dan kelancaran berlalu lintas dan tercatat pada pasal 48 – 55 UU No. 22/2009. Proses pendaftaran yang berjalan di Dinas Perhubungan Kabupaten Sukabumi masih terbilang manual dan belum di fasilitasi oleh sistem sehingga pelayanan yang diberikan masih belum maksimal, dengan Jumlah pendaftaran rata-rata 90-100 pendaftar perharinya bahkan bisa melebihi kuota yang di sediakan, pihak Dinas Perhubungan Kabupaten Sukabumi menyediakan waktu pendaftaran mulai dari pukul 08.30 pagi sampai pukul 12.00 siang, namun jumlah pendaftar dan waktu pendaftaran tidak sesuai sehingga menyebabkan petugas loket pendaftaran kewalahan dalam mengatur antrian bahkan sering kali menyebabkan antrian yang panjang, tidak jarang juga ada pendaftar yang tidak kebagian jadwal Uji karena jadwal yang sudah penuh pada hari itu, sehingga harus datang lagi di hari besok nya. Karena berbagai permasalahan tersebut maka akan dibuatlah suatu perancangan enterprise architecture pendaftaran uji kir menggunakan Federal Enterprise Architecture Framework ( FEAF) di Dinas Perhubungan Kabupaten Sukabumi.Hasil dari penelitian ini adalah membuat sebuah perancangan sistem untuk pendaftaran uji kir, berupa model semantic, diagram activity, diagram use case, rancangan arsitektur jaringan, dan rancangan database yang diperlukan untuk pembuatan sistem, serta sebuah sistem pendaftaran uji kir.Kata Kunci: Perancangan Enterprise Architecture, Uji Kir, FEAF ( Federal Enterprise Architecture Framework)